Design of Administration System in Client Side Using Oracle Form Builder - Arb, Ghusoon Idan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper focuses on the creation of a single system for distribution to a team of developers. Oracle Form Builder are popular and made the function of project expansion easier and comparably faster to reduce costs and improve service levels for users. Design of administration system in client side is made available to employees to assist them in the performance of their job duties. Both Oracle Database and MySQL are strong relational database management systems that effectively run great amounts of data. Oracle Database is a full distinct database engine that has successfully passed severe security exams and has excelled in performance benchmarks. With built-in backup for PL/SQL and Java. OracleÂ focusing on Java for next generation commerce applications.